2000
DOI: 10.1046/j.1432-1327.2000.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a direct role of the integrin α2β1 in collagen‐induced tyrosine phosphorylation in human platelets

Abstract: In the present study we have investigated whether the collagen receptor a2b1 (GPIa-IIa; GP, glycoprotein) regulates protein tyrosine phosphorylation in platelets directly through activation of tyrosine kinases or indirectly through modification of the response to GPVI. The interaction of collagen with a2b1 was inhibited in two distinct ways, using the metalloprotease jararhagin, which cleaves the b1 subunit, or the antibody P1E6 which competes with binding of collagen to the integrin. The two inhibitors caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
2
31
1
Order By: Relevance
“…Surprisingly, they reported that the peptide has no effect on functional responses and tyrosine phosphorylation in platelet suspensions despite being able to bind to the integrin under these conditions. 106 Hers et al 94 made a similar conclusion through examination of the actions of a number of ␣ 2 ␤ 1 -specific antibodies in platelet suspensions, many of which have been shown to activate the integrin in other systems.…”
Section: Does the Integrin ␣ 2 ␤ 1 Generate Intracellular Signals?mentioning
confidence: 87%
See 2 more Smart Citations
“…Surprisingly, they reported that the peptide has no effect on functional responses and tyrosine phosphorylation in platelet suspensions despite being able to bind to the integrin under these conditions. 106 Hers et al 94 made a similar conclusion through examination of the actions of a number of ␣ 2 ␤ 1 -specific antibodies in platelet suspensions, many of which have been shown to activate the integrin in other systems.…”
Section: Does the Integrin ␣ 2 ␤ 1 Generate Intracellular Signals?mentioning
confidence: 87%
“…While some authors reported that inhibition of ␣ 2 ␤ 1 markedly reduced or abolished adhesion and aggregate formation in stasis and flow, [88][89][90] others found only minor effects of such treatment on adhesion to collagen [91][92][93] and collagen-induced aggregation. 94 Several factors are likely to have contributed to these differences, including the nature of the response under investigation; the experimental conditions, notably the presence or absence of plasma; and the preparation of collagen. These are each discussed in further detail in this section.…”
Section: Role Of Integrin ␣ 2 ␤ 1 In the Adhesion And Aggregation Of mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as described above for platelet aggregation, the presence of integrin ␣ 2 ␤ 1 -mediated activation signals has been challenged by others. 1,11 Thus, we sought to characterize the integrin ␣ 2 ␤ 1 -mediated signals that lead to platelet spreading in this study. Platelets adhere to collagen, then extend projections, and finally form curtainlike extensions between the projections during the process of spreading.…”
Section: Introductionmentioning
confidence: 99%
“…22,37 However, it is not clear how far the integrin is directly responsible for signaling leading to platelet activation, because anti-␣ 2 ␤ 1 antibodies neither block tyrosine phosphorylation nor activation of FAK induced by fibrillar collagen, when aggregation rather then adhesion is dominant. 25,38,39 We also observed that overall tyrosine phosphorylation in control or PP2-treated adherent platelets was unchanged by the 6F1 antibody, even though this antibody decreased adhesion to 17% and 15%, respectively (data not shown). We reported earlier that changes in cGMP levels can influence platelet adhesion to collagen 36 and that PKC is involved in activating the ␣ 2 ␤ 1 integrin and enabling firm adhesion.…”
Section: Collagen Receptors Involved In Signaling During Adhesionmentioning
confidence: 64%